Dampak Kebijakan Schengen Uni Eropa Terhadap Euroscepticism di Nordik - Sari, Putri Novita (Global and Policy Journal of International Relations, 2017)
ABSTRACTIn 2014 the number of issues discussing immigrants in the EU is 24% and by 2015 by 38%. And Euroscepticism is due to immigrants in Sweden at 48% while in Denmark it is 55% and both are Nordic countries. This is the reason why this paper is made. This paper will discuss the impact of Schengen policy on Euroscepticism in the Nordic. The approach that will be used is Globalization, welfare state and national interest. Globalization will be implemented in the form of schengen policy that causes the immigrant crisis in the Nordic. Nordic became the main goal of immigrants because it is a welfare state that has social security. And social security is a national interest maintained by native Nordic communities from immigrant immigrants to emerge euroscepticism. The effect was that a border control policy was made by the Nordic governments to press the immigrants who came and set up border patrols between the Nordic countries themselves.Keywords: Schengen, Immigrant, Euroscepticism, Nordic, Border ControlDOI: https://doi.org/10.33005/jgp.v5i02.1893